WZORZEC UMOWY SPÓŁKI JAWNEJ I SPÓŁKI KOMANDYTOWEJ - Gawrysiak-Zabłocka, Aleksandra (Zeszyty Prawnicze, 2016)
E-forms for General Partnership and Limited Partnership Agreements in Polish Law Summary Since the latest amendment of the Polish Code of Commercial Part nerships and Companies (CCPC) entered into force on 15th January 2015 it has been possible to set up a general partnership or a limited partnership using a standardised electronic form for the agreement. The article contains an analysis of the new regulations. Though the idea to use electronic communication in setting up partnerships is a welcome measure, there is no doubt that it would have been better if the forms for general partnership and limited partnership agreements were annexes o the CCPC instead of annexes to regulations issued by the Minister of Justice. Moreover, some of the arrangements in these forms call for criticism. The provisions in e-forms should be no different from those in he CCPC. The regulations in the e-forms for partnership of indefinite duration or for method of representation of partnership should be amen ded. Partners should also be given more freedom in some other issues, e.g. in determining how they are to participate in the allocation of loss.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />